Auto focus alarm system / Mohammad Badrul Shah Salehan & Muhammad Arif Ngasri - Salehan, Mohammad Badrul; Ngasri, Muhammad Arif (2015)
This Auto Focus Alarm System project is about home security system that can focus where is the actual position of the robber when they come into our home. This alarm system also can detect where is the robber come from. The LCD will display the location the robber had broke in. After the alarm is activated, the user need to enter the password to make the system active. Arduino controller mega is used to program the switch, LCD, motion sensor, buzzer servo motor. When a motion is detected in the house, the alarm system will be triggered. For example, when the robber came into the house through the window at the kitchen, the camera will focus to the robber and started recording and the lamp will light up. This Auto Focus Alarm System are more effective and smart to use at any building because this system is low power consumption. This is proven by the camera because the camera will not active and do recording at 24 hours. The camera will turn on and active when there are any robbers detected.